2021
DOI: 10.3389/fgwh.2021.694808
|View full text |Cite
|
Sign up to set email alerts
|

Early Pup Removal Leads to Social Dysfunction and Dopamine Deficit in Late Postpartum Rats: Prevention by Social Support

Abstract: Offspring interaction is among the most highly motivated behaviors in maternal mammals and is mediated by mesolimbic dopamine (DA) system activation. Disruption or loss of significant social relationships is among the strongest individual predictors of affective dysregulation and depression onset in humans. However, little is known regarding the effects of disrupted mother–infant attachment (pup removal) in rat dams. Here, we tested the effects of permanent pup removal in rat dams, which were assigned to one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Recent studies indicate that postpartum rats show transient changes in dopaminergic activity which are linked with the expression of depressive-like behaviors ( Rincón-Cortés and Grace, 2019 ). The unique social stressor of pup removal further alters dopaminergic activity in postpartum dams, resulting in a decrease of spontaneously active dopamine neurons, which can be rescued by paring housing two pup-separated dams together ( Rincón-Cortés and Grace, 2021 ). These results suggest provide initial evidence that social support may attenuate the effect of stressors by restoring dopamine neuron activity.…”
Section: Using Inter-individual Variability To Predict Mental Health ...mentioning
confidence: 99%
“…Recent studies indicate that postpartum rats show transient changes in dopaminergic activity which are linked with the expression of depressive-like behaviors ( Rincón-Cortés and Grace, 2019 ). The unique social stressor of pup removal further alters dopaminergic activity in postpartum dams, resulting in a decrease of spontaneously active dopamine neurons, which can be rescued by paring housing two pup-separated dams together ( Rincón-Cortés and Grace, 2021 ). These results suggest provide initial evidence that social support may attenuate the effect of stressors by restoring dopamine neuron activity.…”
Section: Using Inter-individual Variability To Predict Mental Health ...mentioning
confidence: 99%
“…The second model consists of manipulating the dam’s physical environment by reducing the amount of bedding material within the dam’s home cage (i.e., resource scarcity; Ivy et al, 2008 ). We have recently shown that both models converge in disrupting a variety of behaviors in the dam, including maternal and depression-relevant behaviors, and attenuating mesolimbic DA system function (Rincón-Cortés and Grace, 2021 , 2022 ).…”
Section: Da Deficits In Novel Rodent Models Useful For the Study Ppd ...mentioning
confidence: 99%
“…Because we cannot measure grief in rodents, we focus on the increased depression-related phenotypes resulting from permanent pup removal. Permanent pup removal increases passive FST coping responses (i.e., immobility) and reduces social motivation during the late postpartum period in rat dams (Pawluski et al, 2009 ; Rincón-Cortés and Grace, 2021 ). These behavioral effects overlap with those observed in female rodent models relevant to depression, including stress-based, pharmacologically-induced and genetic models (Iniguez et al, 2018 ; Newman et al, 2019 ; Lima et al, 2022 ), as well as in PPD rodent models employed during the postpartum (Perani and Slattery, 2014 ; Li and Chou, 2016 ; Qiu et al, 2020 ; Mir et al, 2022 ).…”
Section: Da Deficits In Novel Rodent Models Useful For the Study Ppd ...mentioning
confidence: 99%
See 2 more Smart Citations